Awareness and knowledge of cyberethics: A comparative study of preservice teachers in Malta, Norway, and Spain - Josephine Milton (Oslo and Akershus University College of Applied Sciences, 2021)
This paper explores the knowledge and understanding of cyberethics held by preservice teachers across three European countries. The study was conducted via an online survey and yielded a total of 1,131 responses from preservice teachers in Spain, Norway, and Malta. The facets of cyberethics included in this study were specifically related to behaving responsibly online, safeguarding privacy, respecting copyright, seeking consent of third parties before posting images or videos on social media platforms, and considering their own professional identity as future teachers when posting images or videos online. The findings indicate that preservice teachers reported similar levels of competence in both applying copyright and respecting privacy rules. However, this varied across countries, with preservice teachers in Malta and Norway reporting higher levels of knowledge and awareness than their counterparts in Spain. Malta had the largest number of participants who reported that they ‘always’ considered the potential impact that posting media online may have on their careers, followed by Norway. Spain had the largest number of preservice teachers who stated that they rarely or never thought about this impact on their teaching career. Our findings highlight the need for student teachers’ knowledge of cyberethics to be prioritised during ITE, especially within the framework of developing a professional digital identity. In light of our findings, we recommend that all ITE programmes include digital competence and cyberethics components in their curricula. This would enable preservice teachers to develop an emerging professional and digital identity to face the challenges of becoming teachers in the 21st century.